2023
DOI: 10.1146/annurev-neuro-092822-083410
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of PTBP1 Inhibition, If Any, Is Not Attributed to Glia-to-Neuron Conversion

Abstract: A holy grail of regenerative medicine is to replenish the cells that are lost due to disease. The adult mammalian central nervous system (CNS) has, however, largely lost such a regenerative ability. An emerging strategy for the generation of new neurons is through glia-to-neuron (GtN) conversion in vivo, mainly accomplished by the regulation of fate-determining factors. When inhibited, PTBP1, a factor involved in RNA biology, was reported to induce rapid and efficient GtN conversion in multiple regions of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…On the other hand, studies using AAV vectors have also presented data on the generation of retinal ganglion cells upon combined co-expression of Math5/Atoh7 and Brn3b/Pou4f2 [474] and the downregulation of Ptbp1 [475] or photoreceptors through two AAV injections, one with beta-catenin to stimulate proliferation and the other with Otx2, Crx, and Nrl [476]. However, the demonstration of the lack of specificity of the alleged glial promoters raised concerns in some of these studies and highlighted the need for proper strategies for tracing the MG as the cell of origin in protocols for MG to neuron reprogramming [477][478][479][480]. Research groups are also searching for alternative or complementary tools for MG reprogramming, such as investigating ways to identify novel cell-type specific regulatory regions to drive gene expression [481], modifications in AAV-carried sequences testing modifications in AAV-carried sequences [482], or screening compounds to increase the neurogenic reprogramming of the MG [483].…”
Section: Cell Reprogrammingmentioning
confidence: 99%
“…On the other hand, studies using AAV vectors have also presented data on the generation of retinal ganglion cells upon combined co-expression of Math5/Atoh7 and Brn3b/Pou4f2 [474] and the downregulation of Ptbp1 [475] or photoreceptors through two AAV injections, one with beta-catenin to stimulate proliferation and the other with Otx2, Crx, and Nrl [476]. However, the demonstration of the lack of specificity of the alleged glial promoters raised concerns in some of these studies and highlighted the need for proper strategies for tracing the MG as the cell of origin in protocols for MG to neuron reprogramming [477][478][479][480]. Research groups are also searching for alternative or complementary tools for MG reprogramming, such as investigating ways to identify novel cell-type specific regulatory regions to drive gene expression [481], modifications in AAV-carried sequences testing modifications in AAV-carried sequences [482], or screening compounds to increase the neurogenic reprogramming of the MG [483].…”
Section: Cell Reprogrammingmentioning
confidence: 99%
“…On the other hand, studies using AAV vectors have also presented data on the generation of retinal ganglion cells, upon combined coexpression of Math5/Atoh7 and Brn3b/Pou4f2 [453] and downregulation of Ptbp1 [454]; or photoreceptors through two AAV injections, one with beta-catenin to stimulate proliferation and the other with Otx2, Crx and Nrl [455]. However, demonstration of the lack of specificity of alleged glial promoters raised concerns on some of these studies and highlighted the need for proper strategies for tracing MG as the cell of origin in protocols for MG to neuron reprogramming [456][457][458][459]. Groups are also searching for alterative or complementary tools for MG reprogramming such as investigating ways to identify novel cell-type specific regulatory regions regions to drive gene expression [460], modifications in AAV-carried sequences testing modifications in AAV-carried sequences [461], or screening compounds to increase neurogenic reprogramming of MG [462].…”
Section: Cell Reprogrammingmentioning
confidence: 99%
“…Nevertheless, the reprogramming achieved through PTPB1 deletion remains a subject of controversy ( Chen, 2021 ; Wang and Zhang, 2022 , 2023 ; Hao et al, 2023 ; Hoang et al, 2023 ). Hoang’s research, employing a combination of genetic lineage tracing, single-cell RNA sequencing (scRNA-seq), and electroretinogram analysis, has demonstrated that the selective induction of either heterozygous or homozygous loss-of-function mutants of PTBP1 in adult retinal Müller glia does not result in any observable level of neuronal conversion ( Hoang et al, 2022 ).…”
Section: Müller Cell Reprogramming In Mammalsmentioning
confidence: 99%